Great crimes - Escott, John (Oxford University Press, 1998)
Most of us love reading about crime in the newspapers, and reading stories about Sherlock Holmes and the other great detectives. This book looks at some of the great crimes of history - crimes like the Lindbergh kidnapping and the Mona Lisa robbery. It also looks at some great criminals, like the poisoner Dr Crippen. Most of these crimes were solved, but some, like the assassination of President Kennedy, still hold their mysteries